Phospho-SIM and exon8b of PML protein regulate formation of doxorubicin-induced rDNA-PML compartment - Hornofova, Terezie; Pokorna, Barbora; Hubackova, Sona Stemberkova; Uvizl, Alena; Kosla, Jan; Bartek, Jiri; Hodny, Zdenek; Vasicova, Pavla (DNA repair, 2022)
Repetitive sequences are among the most unstable regions in the eukaryotic genome and defects in their maintenance correlate with premature aging and cancer development. Promyelocytic leukemia protein (PML) induces accumulation of proteins at distinct nuclear sites, thereby affecting a plethora of processes including DNA repair or maintenance of telomeres. Doxorubicin, the broadly used chemotherapeutic compound, induces formation of PML-nucleolar associations (PNAs). Nevertheless, molecular factors affecting formation of PNAs are still largely unknown. Here we show that PNAs can accumulate ribosomal DNA (rDNA) and, after restoration of RNA polymerase I activity, these structures transfer a fraction of rDNA outside the nucleolus. Mutagenesis of PML isoforms revealed that this process depends on the SUMO-interacting motif and adjacent serine-rich region, and is enhanced by exon8b present exclusively in PML IV isoform. Moreover, we demonstrate that PNAs formation is also regulated by p14ARF/p53 tumor suppressors and casein kinase 2. Our data elucidate how PML nucleolar compartment is assembled, bring the first evidence of PML interacting with rDNA, and show the PML-dependent translocation of rDNA away from the nucleolus.
Keywords: Protein Isoforms; jaderné proteiny; Doxorubicin; Peptide Nucleic Acids; doxorubicin; nádorové supresorové proteiny; Nucleolus; PML; protein - isoformy; rDNA; DNA, Ribosomal; Nuclear Proteins; ribozomální DNA; peptidové nukleové kyseliny; Tumor Suppressor Proteins; Phospho-SIM; P14(ARF)